PESONA BUDAYA DI DESA WISATA WAYANG SIDOWARNO KECAMATAN WONOSARI, KABUPATEN KLATEN, JAWA TENGAH - Teddy Chandra; Sukarno Wibowo (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2026)
Cultural Charm in Sidowarno Wayang Tourism Village, Wonosari District, Klaten Regency, Central Java is a study conducted as an effort to identify various cultural potentials found in Sidowarno village. The research questions posed in this study are: 1) how is the description of the Sidowarno Wayang tourism village; and 2) how is the description of culture as a tourist attraction in the Sidowarno Wayang tourism village. This research was conducted using qualitative research methods. Data collection techniques used in this study were literature studies, observations and interviews. The data obtained were analyzed descriptively. The results of the study show that Sidowarno Village, located in Wonosari District, Klaten Regency, Central Java Province, is a tourist village that continues to develop with the advantage of cultural tourism potential. As a wayang tourism village, Sidowarno Village has a diverse cultural wealth such as shadow puppets, tatah sungging art, jemparingan, and punokawan dance which are able to become tourist attractions in attracting domestic and foreign tourists to come to Sidowarno Village.